Analisis Numerik Kuat Lentur Dan Pola Retak Balok T Semi Pracetak - Ariadi, Koko Putra; Ismeddiyanto, Ismeddiyanto; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Semi precast reinforced concrete (RC) used as an alternative in developing infrastructure is an excellent innovation, because of the advantages of this system can significantly reduced cost and construction time. Semi precast reinforced concrete (RC) beam is a combination of precast concrete which consists of the support beam and curve tile with the cast in place concrete. The elements are applied as a T-beam because of the interaction between the platesand the beams become unity. The study aims to identify the effect of the support beam and curve tile on the T-beam towards load-deflection relationship, curvature-moment and crack pattern caused by pure bending moments. The results showed that the load attained from finite element analysis was 56,664 kN while the load attained from strip method was 56,810 kN. Meanwhile, the stiffness value of finite element analysis was 1,206 kN/mm while the loadattained from strip method was 1,210 kN/mm. The collapsed pattern on the T-beam analyzed by using Extended Finite Element Method (XFEM) was a pure bending crack at the most significant bending moment region. The crack pattern showed the crack on the tension side of the beam in the direction of the stirrups.Key words : T-Beam, Semi Precast, FEA, Abaqus CAE, Bending Moment, Curve Tile